Synthesis and In Vitro Evaluation of a Scandium-44 Radiolabeled Nanobody as a PD-L1 PET Imaging Probe - Viktoria E. Krol; Aditya Bansal; Manasa Kethamreddy; Jason R. Ellinghuysen; Daniel J. Vail; Fabrice Lucien-Matteoni; Haidong Dong; Sean S. Park; Mukesh K. Pandey (Pharmaceutics)
Background/Objective: Noninvasive PET imaging-based assessment of PD-L1 expression is of high clinical value for better patient selection and treatment response rates to PD-L1 immunotherapies. Due to their shorter biological half-life and faster clearance from the blood pool, radiolabeled antibody fragments are an attractive alternative for imaging than their full-length IgG counterpart. This work investigated the radiosynthesis and in vitro cell uptake of anti-PD-L1-B11-nanobody radiolabeled with 44Sc (t1/2 = 4.04 h) as an alternative to anti-PD-L1-B11-IgG, better suited for longer half-life radioisotopes such as 89Zr (t1/2 = 78.41 h). Methods: The proteins were conjugated with p-SCN-Bn-DTPA and radiolabeled at room temperature with 44Sc, achieving a radiochemical yield of a RCY of 94.8 ± 3.1% (n = 3) for [44Sc]Sc-B11-IgG and 73.6 ± 12.1% (n = 3) for [44Sc]Sc-B11-nanobody, before purification. Results: Significantly higher uptake in the PD-L1+ cells than PD-L1KO cells was observed for both probes. However, high non-specific uptake, particularly of the radiolabeled B11-nanobody, was also observed which may negatively impact its potential as a molecular imaging probe. Conclusions: Due to the high non-specific uptake in vitro, the 44Sc radiolabeled nanobody was not progressed to further in vivo evaluation. These results should, however, not discourage future evaluations of other nanobody based probes radiolabeled with 44Sc, due to their well-matched biological and physical half-life.